(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Food Processing involves any type of value addition toagricultural or horticultural produce and also includes processes such asgrading, sorting and packing which enhance shelf life of food products. Indiais one of the world’s major food producers but account for less than 2% ofinternational food trade. This indicates best scope for both investors andexporters. The FPI is of enormous significance for India’s development becausethe vital linkages and synergies that promotes between the two pillars of theeconomy namely industry and agriculture. No doubt the FPI in India is onassured track of growth and profitability over the coming decades. Greenrevolution has transformed India from a land of shortage to a land of surplus.India is presently the world’s second largest producer of food and has thepotential of being the biggest with developing food and agricultural sector.Growing economy, surplus food and changing life style has shifted theconsumption pattern, from cereals to more varied and nutritious diet of fruitand vegetables, milk, fish, meat and poultry products. This gradual progressionhas given rise to the food processing industry in India. The food processingsector in the country with its vast potential has emerged as one of the majordriver of economic growth and is after hailed as a sunrise industry. However,market experts are of the opinion that in future, the food products is going tocontribute majority towards India’s GDP growth. In this paper attempt is madeto explore the growth opportunities and major challenges to FPI in India.